1 × 4 optical switch based on electrowetting. Issue 10 (20th November 2017) - Wang, Jin‐Hui; Li, Lei; Yuan, Rong‐Ying; Wang, Qiong‐Hua
Abstract: In this paper, we report a 1 × 4 optical switch using deformable liquid droplet. The deformation is produced by the electrowetting on dielectric phenomenon. The device consists of a dyed oil and a transparent conductive liquid sealed in a transparent cylinder. The top glass cover of the device has four independently addressable electrodes for the actuation of the liquid dome in each direction. In the voltage‐off state, incident light is absorbed by the dyed liquid. When the voltage is applied to the liquid, the dome of the transparent liquid is uplifted and then spreads to four different directions because of the effect of electrostatic force. Accordingly, the transparent liquid pushes the dyed oil out to form a light path. The device with simple structure can freely control multiple switch apertures through changing the driven voltage. In addition, we analyze the electro‐optical characteristics such as transmittance, response time (open time ~110 ms, close time ~160 ms), contrast ratio (~661:1). Abstract : In this paper, we report a 1 × 4 optical switch using deformable liquid droplet. The device with simple structure can freely control multiple switch apertures through changing the driven voltage. We analyze the electro‐optical characteristics such as transmittance, response time (open time ~110 ms, close time ~160 ms), and contrast ratio (~661:1). Figure 1 depicts the 3D visualization and physical map of the device.